2016
DOI: 10.1016/j.cell.2016.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Functional Dissection of Common Genetic Variation Affecting Red Blood Cell Traits

Abstract: Summary Genome-wide association studies (GWAS) have successfully identified thousands of associations between common genetic variants and human disease phenotypes, but the majority of these variants are non-coding, often requiring genetic fine-mapping, epigenomic profiling, and individual reporter assays to delineate potential causal variants. We employ a massively parallel reporter assay (MPRA) to simultaneous screen 2756 variants in strong linkage-disequilibrium with 75 sentinel variants associated with red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
397
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(421 citation statements)
references
References 57 publications
21
397
2
1
Order By: Relevance
“…It is likely that common genetic variants associated with small changes in erythrocyte production act by slightly altering the binding and activity of GATA1 and co-factors, resulting in mild to moderate changes in the expression of target genes. 15 In the study herein we demonstrated that the clinical features of the case B-II.2 are the result of a complex genotype SEC23B-GATA1, suggesting a novel genetic etiology underlying CDAII. We described a GATA1 polymorphism as a genetic modifier, which exacerbates the phenotype induced by mutations in GATA1-dependent genes.…”
mentioning
confidence: 85%
“…It is likely that common genetic variants associated with small changes in erythrocyte production act by slightly altering the binding and activity of GATA1 and co-factors, resulting in mild to moderate changes in the expression of target genes. 15 In the study herein we demonstrated that the clinical features of the case B-II.2 are the result of a complex genotype SEC23B-GATA1, suggesting a novel genetic etiology underlying CDAII. We described a GATA1 polymorphism as a genetic modifier, which exacerbates the phenotype induced by mutations in GATA1-dependent genes.…”
mentioning
confidence: 85%
“…58 MPRAs have also been used to simultaneously test thousands of variants associated with eQTLs 22 or variants in linkage disequilibrium with lead SNPs from GWASs for red blood cell traits. 59 Another noteworthy adaptation of MPRAs is population-scale self-transcribing active regulatory region sequencing (POPSTARR), in which candidate regulatory elements from numerous individuals are cloned via DNA sequence capture and tested in parallel. 60 However, regulatory grammar is not fully understood, and MPRAs take transcriptional regulatory elements out of their genomic and native chromatin context.…”
Section: Annotating Every Possible Variant In Disease-related Functiomentioning
confidence: 99%
“…For disease-associated eQTLs, understanding the relationship between the quantitative expression effect in the cells and disease risk will be important for understanding molecular mediators of disease risk. Finally, the recent development of experimental approaches such as MPRA (Tewhey et al 2016;Ulirsch et al 2016), STARR-seq (Arnold et al 2013;Vockley et al 2015), and CRISPR genome editing assays (Canver et al 2015;Wright and Sanjana 2016) has created demand for translating summary statistics of eQTL mapping to quantifications that are interpretable as reflecting molecular events in the cell. Our biologically interpretable estimates of cis-eQTL effect sizes from population data can be directly compared with in vitro quantification of regulatory variant effects.…”
Section: Genome Research 1879mentioning
confidence: 99%
“…Estimating the relative effect of eQTL alleles on expression levels has applications in computational functional genetics analysis, as well as in analysis of genetic regulatory variants by experimental assays such as genome editing (Arnold et al 2013;Canver et al 2015;Vockley et al 2015;Tewhey et al 2016;Ulirsch et al 2016;Wright and Sanjana 2016). However, thus far there has been no consensus definition for eQTL effect size, with each study defining its own measure for quantifying regulatory effect size.…”
mentioning
confidence: 99%